2014
DOI: 10.1111/cmi.12270
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of promiscuous endothelial binding by P lasmodium falciparum ‐infected erythrocytes

Abstract: SummaryThe adhesion of infected red blood cells (iRBCs) to human endothelium is considered a key event in the pathogenesis of cerebral malaria and other life‐threatening complications caused by the most prevalent malaria parasite Plasmodium falciparum. In the past 30 years, 14 endothelial receptors for iRBCs have been identified. Exposing 10 additional surface proteins of endothelial cells to a mixture of P. falciparum isolates from three Ghanaian malaria patients, we identified seven new iRBC receptors, all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Endothelial cytoadhesion and the binding capacities of various laboratory strains and patient isolates of P. falciparum have been mainly investigated under static conditions 6,31,32 . This is classically achieved by directly incubating IEs with cells or recombinant receptors of interest 8,16,33,34 . Finally, adherent IEs are counted manually.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cytoadhesion and the binding capacities of various laboratory strains and patient isolates of P. falciparum have been mainly investigated under static conditions 6,31,32 . This is classically achieved by directly incubating IEs with cells or recombinant receptors of interest 8,16,33,34 . Finally, adherent IEs are counted manually.…”
Section: Resultsmentioning
confidence: 99%
“…CHO-745 cells defective in glycosaminoglycan biosynthesis (American Type Culture Collection (ATCC); no. CRL-2242) were transfected and cultured as previously described 8,31,33 . CHO-745 cells transfected with GFP, CD36, ICAM-1, P-selectin, and CD9 were used.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a low constitutive expression of EPCR was observed particularly in the brain. These findings might serve as an explanation for the organ-specific pathology in CM, which is induced by cytoadherence of Plasmodium -infected red blood cells (iRBCs) in brain microvessels to a wide range of additional receptors [5] . It was suggested that a low capacity of EPCR to activate protein C caused by adherence of iRBCs and adjacent cleavage of EPCR could provoke a proinflammatory and procoagulant state in affected tissues.…”
Section: Introductionmentioning
confidence: 97%
“…With many varied PfEMP1s in the genome, a major question has therefore been whether specific PfEMP1s, with specific receptor-binding phenotypes, are associated with particular severe disease syndromes. Indeed, PfEMP1 domains have been suggested to interact with a wide range of different human protein and carbohydrate ligands [24,25]. This raises several questions.…”
Section: Do Anti-disease Immunogens Have a Place In Future Malaria Vamentioning
confidence: 99%